PEMBANGKIT LISTRIK TENAGA ANGIN DENGAN SISTEM MEKANIK VIBRASI PITA DAWAI - Aprinasyah, Angga; R., Gilang; R., Tiar; K., Tia; Susanto, K. (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Energy is an essential requirement in peoples lives. When viewed from the source of the current world energy supply, and as the major sources, oil and gas resources are limited and will run out at some point. Various studies were conducted to find energy sources beyond oil and gas. One of the alternative energy sources that can be developed is wind power. This study utilizes wind using ribbon string vibration systems. Wind is used to vibrate the ribbon that had been paired with a magnetic coil to produce an electric current. The lowest average wind speed is 6.67m/s obtained at 1.3298 watts of electrical power (voltage of 11.83 volts; 112.41mA). These results can be used to turn on the LED at 6 volts with a current of 30mA. To anticipate the absence of wind diving for 3 hours, the use of batteries at 6 volts with 1,800Ah currents can be filled by